1996
DOI: 10.1007/bf01955265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cortical thickness and bone density by roentgen microdensitometry in growing males and females

Abstract: This study provides the normative data of bone mass in growing individuals by making use of a reasonably accurate and easily available technique. The results obtained indicate that most of the differences between males and females and the changes with age are related to changes in skeletal dimension rather than density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 16 publications
(19 reference statements)
1
35
0
Order By: Relevance
“…On the other hand, it has been reported that QUS moderately correlated with BMD (r ϭ 0.40 -0.70) assessed by densitometric techniques (11,12,39). Therefore, we cannot exclude that the rise of AD-SoS values in phalanxes during childhood and adolescence may reflect, at least in part, a small increase in cortical BMD as found at the second metacarpus by roentgen microdensitometry (40), or in trabecular BMD as showed at vertebral bodies in late puberty by quantitative computed tomography, reflecting an increase in trabecular number or thickness (28,41). In this regard, a histomorphometric study on iliac bone specimens in growing children (1.5-22.9 y) demonstrated an age-dependent increase in both cortical width and trabecular bone volume, the latter being caused by an increase in trabecular thickness (42).…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, it has been reported that QUS moderately correlated with BMD (r ϭ 0.40 -0.70) assessed by densitometric techniques (11,12,39). Therefore, we cannot exclude that the rise of AD-SoS values in phalanxes during childhood and adolescence may reflect, at least in part, a small increase in cortical BMD as found at the second metacarpus by roentgen microdensitometry (40), or in trabecular BMD as showed at vertebral bodies in late puberty by quantitative computed tomography, reflecting an increase in trabecular number or thickness (28,41). In this regard, a histomorphometric study on iliac bone specimens in growing children (1.5-22.9 y) demonstrated an age-dependent increase in both cortical width and trabecular bone volume, the latter being caused by an increase in trabecular thickness (42).…”
Section: Discussionmentioning
confidence: 76%
“…Radiographs of the left hand and wrist, taken before starting GH treatment and at final height, were used to assess bone age by the method of Greulich and Pyle (13) and also to evaluate metacarpal bone geometry. We determined firstly the metacarpal index (MI), which is a relative measure of the thickness of the 2nd metacarpal cortical bone, taken at its narrowest site, as previously described (14). The values were then converted to standard deviation score (MI SDS) according to our normative data (14).…”
Section: Methodsmentioning
confidence: 99%
“…We determined firstly the metacarpal index (MI), which is a relative measure of the thickness of the 2nd metacarpal cortical bone, taken at its narrowest site, as previously described (14). The values were then converted to standard deviation score (MI SDS) according to our normative data (14). We also evaluated the inner and outer diameter at the same site and calculated the total, cortical and endomedullary cross-sectional area (CSA).…”
Section: Methodsmentioning
confidence: 99%
“…This method makes use of the same X-ray pictures which are routinely obtained for the assessment of bone age, as previously described (20). The radiographs were taken with a graduated aluminium reference standard calibrated versus a hydroxyapatite phantom positioned at the level of the styloid process of the radius.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that there is a highly significant linear correlation between the volumetric density, calculated by dividing the BMC by both bone width and depth, and the volumetric density, calculated assuming a circular cross-sectional area of the two bone segments, with an interception and a slope very close to zero and one respectively. The data have been plotted against our published reference data (20) and are expressed as SDS for sex and bone age, since bone mineral density is known to correlate better with bone age than with chronological age (22). Results are expressed as means Ϯ S.D.…”
Section: Methodsmentioning
confidence: 99%